An evaluation of the final year dental students' geriatric oral health community programme. - Haslina Rani,; Nurul Asyikin Yahya,; Rahimah Abdul Kadir, (Penerbit Universiti Kebangsaan Malaysia, 2011)
The objective of this study was to evaluate the effectiveness of the teaching-learning process involved in the geriatric oral health community programme for final year dentistry students which was introduced by the Faculty of Dentistry, Universiti Kebangsaan Malaysia. The geriatric oral health community programme formed part of the curriculum for final year students and involved the division of the students into small groups. The groups were facilitated by their instructors to prepare an activity which was to be conducted at various community geriatric institutions. These group activities required the students to apply the oral health planning and promotion concepts they had been taught prior to the activity. At the end of an eight-week long preparation period, the students implemented a day-long programme at the institution. The effectiveness of the teaching-learning process involved in the programme was evaluated using a self-administered questionnaire measuring three segments: fulfilment of programme objectives, assessment of facilitators and programme processes and overall satisfaction regarding the conducted programme. Data was collected two weeks after the completion of each student group’s visit. Fifty of the total fifty-two participating students (96.2%) responded. Of these, forty-nine students (98%) were either ‘somewhat satisfied’ or ‘satisfied’ with the programme conducted. The majority of the students agreed that the programme had managed to achieve the following objectives: (1) sensitized them towards harbouring a caring attitude towards the elderly, (2) enabled them to better their interaction with the elderly, and (3) made them realize the importance of teamwork in executing a community project. Despite the certain administrative weaknesses encountered in conducting the program, the students agreed with the relevance and importance of the inclusion of community geriatric dental education in their curriculum.